Book Review: The Financial Diaries - Barbara O'Neill (Journal of Financial Therapy, 2018)
Researchers and practitioners will gain valuable insights into the financial insecurity experienced by many American families after reading this 233-page book by Jonathan Morduch and Rachel Schneider. Morduch is a professor at NYU and Schneider is senior vice president at the Center for Financial Services Innovation. The meticulously referenced book (46 pages are notes and a bibliography) describes a study of family finances.
Keywords: book review; financial therapy